2013
DOI: 10.1088/1612-2011/10/3/035401
|View full text |Cite
|
Sign up to set email alerts
|

Impact of incorporated anatase nanoparticles on the second harmonic generation in KDP single crystals

Abstract: The second harmonic generation efficiency was studied for the single crystalline potassium dihydrogen phosphate matrix with incorporated TiO2 nanocrystals in the field of the mode-locked Nd:YAG laser pulses. For the first time the frequency conversion efficiency gain was observed for KDP:TiO2 single crystal (SC) instead of KDP SC due to the internal self-focusing effect of the pump beam caused by the giant cubic nonlinear optical response of the embedded nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…in laser fusion facilities . However, one of the main shortcomings of KDP crystals is their relatively low quadratic susceptibility . Another limiting factor in the use of KDP in third harmonic generation is its susceptibility to laser damage, a process that couples light absorption with thermal and mechanical effects .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…in laser fusion facilities . However, one of the main shortcomings of KDP crystals is their relatively low quadratic susceptibility . Another limiting factor in the use of KDP in third harmonic generation is its susceptibility to laser damage, a process that couples light absorption with thermal and mechanical effects .…”
Section: Introductionmentioning
confidence: 99%
“…A promising trend in the development of up‐to‐date functional optical materials based on dielectrics is incorporation of tailoring impurities into the crystalline matrixes of traditional nonlinear optical materials . Thus, search for nonlinear optical media possessing high conversion efficiency of laser radiation stimulated creation of composite materials based on KDP dielectric matrix doped with organic molecules or nanoparticles (NPs) . These studies were aimed at correlating the structural properties to the nonlinear responses, the ultimate goal being the possibility of “tuning” the structure to enhance the NLO properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of titanium dioxide nanoparticles (anatase) into KDP crystal matrix has been shown to enhance the efficiency of second harmonic generation in KDP:TiO 2 up to 70% in comparison with pure KDP . The observed effect is caused by the interaction between the quadratic nonlinear optical response of the matrix and the cubic nonlinear optical response of TiO 2 nanoparticles . However, the peculiarities of the inherent structure of these composite systems, their optical properties and the effects, which characterize such materials in the capacity of optical medium, have not been investigated in detail so far.…”
Section: Introductionmentioning
confidence: 63%
“…KCl, oxalic acid, Al 2 O 3 , amaranth, rhodamine B, methyl orange, Lglutamic acid, L-histidine, L-valine [8][9][10][11]. Recently, the effect of TiO 2 (prepared as nanoparticles) on the functional properties of KDP single crystals have been studied [12][13][14][15][16]. It has been reported that the composite system KDP:TiO 2 has giant nonlinear optical response.…”
Section: Introductionmentioning
confidence: 99%